An Analysis of Students’ Perception Using Kahoot Game in Vocabulary Classroom (Undergraduate Conference on Applied Linguistics, Linguistics, and Literature, 2022)
The world of education is currently advancing with increasingly sophisticated technology. There are various education-based online platforms that students and teachers can use as learning media for students. Media such as Kahoot based on educational games can increase students’ enthusiasm during learning. This paper aims to determine students’ perceptions of Kahoot as a learning medium and determine the percentage of students’ interest in using Kahoot. This research is qualitative descriptive for seventh-grade junior high school 2 Tegowanu. The findings show that each student perceives Kahoot, namely positive and negative perceptions. The second finding, led by percentage, is that students feel happy, enthusiastic, and easily remember vocabulary, and Kahoot is useful for students while learning English vocabulary.
Keywords: perception, kahoot, vocabulary